2016
DOI: 10.1007/s10111-016-0379-x
|View full text |Cite
|
Sign up to set email alerts
|

A study of a technological development process: Human factors—the forgotten factors?

Abstract: The aim of this study was to explore how human factors were taken into account in the development of a new type of drilling equipment. This study is part of a larger project on the understanding of human factors in the design and implementation of automated drilling technology. The principal study was a longitudinal study lasting 4 years that involved 43 interviews, offshore and onshore observations, and 2 surveys. MethodThe analysis in this paper is based on 7 informants who were either part of the design tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 53 publications
1
29
0
1
Order By: Relevance
“…Some factors can be considered facilitators or inhibitors of interaction with the communication system: the layout and use of the system [85][86][87]; the support given by the Information Technology team (IT) [88]; the adequacy of the communication channels for the activity [26,37,65,89]; the acceptance of IT [73,81,90]. Communication in the operational area takes place through the technological system instituted by the organization, IT support reduces inhibiting barriers and supports information sharing, stimulates learning, builds knowledge and improves organizational performance [88].…”
Section: E Human Interaction With Ictmentioning
confidence: 99%
“…Some factors can be considered facilitators or inhibitors of interaction with the communication system: the layout and use of the system [85][86][87]; the support given by the Information Technology team (IT) [88]; the adequacy of the communication channels for the activity [26,37,65,89]; the acceptance of IT [73,81,90]. Communication in the operational area takes place through the technological system instituted by the organization, IT support reduces inhibiting barriers and supports information sharing, stimulates learning, builds knowledge and improves organizational performance [88].…”
Section: E Human Interaction With Ictmentioning
confidence: 99%
“…However, we also take great interest in studying the more daily consequences of lack of focus on human factors issues: those that do not generate accidents but result in expensive re-designs, cause minor human errors, breed inefficiency in operations and, most likely, result in some form of dormant, aggregated risk in the organization. After studying the development of new automated drilling technology for offshore oil and gas production, Saetren et al 9 concluded that homogeneous competence involving technical aspects contributed to developers' lack of understanding of the need for sufficient analyses of end-user requirements and of the human tasks that would be affected by the new technology. Consequently, they argued that technological development could benefit from including human factors experts from the project's outset.…”
Section: The Human Factors Discipline -Known Challengesmentioning
confidence: 99%
“…8 Recent studies also investigate new perspectives that may help explain why human factors continue to be marginalized in the development of new technology and systems. 9 In the same timeframe, projects have become a dominant way to organize research, development and construction efforts. The main focus of the project management research has been on challenges, failures and success of projects.…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, the certification of new technologies into the flight deck requires the implementation of a comprehensive Human Factors assessment relating to the design of the device and its integration with other features already on the flight deck. Although Human Factors can, and should, be used throughout a system development (Saetren et al 2016), Human Error Identification (HEI) methods are particularly valuable early within the design cycle to determine potential design-induced errors that may occur within human-machine interaction (Baber and Stanton 1994;Stanton et al 2006Stanton et al , 2013. The findings of such analysis can then be used to provide measures with which to remedy the errors and inform design.…”
Section: Introductionmentioning
confidence: 99%